2008
DOI: 10.1111/j.1365-2818.2008.01961.x
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the distribution of organic components in brachiopod shells by confocal laser scanning microscopy

Abstract: Characterization of the nature and distribution of organic components is crucial to understand shell formation in marine invertebrates. Although several techniques can provide detailed information at high spatial resolution, few of them are non-destructive and informative in a larger structural context. We explore the use of confocal laser scanning microscopy (CLSM) to obtain a better understanding of the distribution of organic components in calcitic shells of brachiopods focusing on perforations (punctae) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Under blue light excitation, it was shown that each GI I region was associated with a couplet of one strongly fluorescing and one poorly fluorescing band. As was reported by Wanamaker et al (2009), the source of the intrinsic fluorescence within the shell of A. islandica is currently not well understood, but it has been suggested that a likely cause of fluorescence in calcitic brachiopods can be attributed to organic macromolecules (Pérez‐Huerta et al , 2008). It was concluded that that the poorly fluorescing band is representative of GI I, and this is consistent with the observations in this study, which demonstrate its increased mineralization.…”
Section: Discussionmentioning
confidence: 97%
“…Under blue light excitation, it was shown that each GI I region was associated with a couplet of one strongly fluorescing and one poorly fluorescing band. As was reported by Wanamaker et al (2009), the source of the intrinsic fluorescence within the shell of A. islandica is currently not well understood, but it has been suggested that a likely cause of fluorescence in calcitic brachiopods can be attributed to organic macromolecules (Pérez‐Huerta et al , 2008). It was concluded that that the poorly fluorescing band is representative of GI I, and this is consistent with the observations in this study, which demonstrate its increased mineralization.…”
Section: Discussionmentioning
confidence: 97%
“…() and Pérez‐Huerta et al . (), fluorescence is triggered by organic macromolecules associated with chitin polysaccharides and proteins. Dark fluorescence colours commonly refer to portions of the shells that are relatively organic matter‐depleted and indicative for periods of slow shell growth.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Currently, the source of the intrinsic fluorescence of A. islandica shells is unknown; A. islandica is known to precipitate its aragonite shell within an organic polymer matrix, which likely includes chitin polysaccharides and proteins (e.g., Addadi et al 2006;Cusack and Freer 2008;Dunca et al 2009). Perez-Huerta et al (2008) suggested that organic macromolecules associated with chitin polysaccharides and proteins in calcitic brachiopods (Terebratalia transversa and Novocrania anomala) are the likely cause of shell fluorescence in these species. The variability in the organic content within A. islandica growth increments has not been studied in any detail, and further work is required to establish the biogeochemical drivers of the fluorescence variability observed here.…”
Section: Discussionmentioning
confidence: 99%